Pengembangan Media GAMAKE (Game Pemadam Kebakaran) untuk Meningkatkan Keterampilan Berpikir Kreatif Anak Usia 5-6 Tahun - Aisyah, Siti; Agustin Ningrum, Mallevi; Matheos Malaikosa, Yes; Rinakit Adhe, Kartika (UIR PRESS, 2024)
This research began with the problem of the lack of digital-based media through GAMAKE media in improving creative thinking skills. Creative thinking is one of the important skills that young children must have and needs to be developed from an early age, especially in children aged 5-6 years. Creative thinking skills can help children solve problems, think critically, and develop new ideas. And also this research aims to determine the feasibility, practicality and effectiveness of the GAMAKE media to improve creative thinking abilities in children aged 5-6 years using GAMAKE media. This type of research uses the R&D (Research and Development). By using the ASSURE development model (Analysis Learner, State Objectives, Select Methods, Media and Materials, Utilize Technology, Media and Materials, Require Learner Participation, Evaluation and Review). In the feasibility test of the media it will be tested on material expert lecturers and media expert lecturers. From the results of the feasibility test for material validation expert lecturers and media validation expert lecturers, the material validation expert lecturers obtained a score of 93%, while media validation expert lecturers received 90%. And the results of product trials at TKM NU 43 Kanjeng Sepuh Sidayu on 18 children aged 5-6 years obtained an assessment from the observation sheet of 86%, so it can be concluded that all statement items were declared valid and suitable to be used as research samples. So it can be concluded that the development of technology-based GAMAKE media by children aged 5-6 years or group B.